Single Beta Models and currency Futures Prices - Thomas H. McCurdy; Ieuan G. Morgan (Queen's University, Department of Economics, 1991)
The conditional capital asset pricing model is applied to foreign currency futures prices, covariance risk being measured relative to excess returns from a broadly diversified international portfolio of equities. Positive time-varying risk premia are found in all five currencies tested when the difference between the US and the average foreign interest rates is used as an instrumental variable for the expected excess return from the common stock portfolio.
Keywords: 330